Laparoscopic ureteral reimplant for ureteral stricture - Soares,Rodrigo S. Q. (2010)
PURPOSE: Evaluate the initial experience of laparoscopic ureteral reimplant for ureteral stenosis. MATERIALS AND METHODS: From January 2004 to June 2008, 10 patients underwent 11 laparoscopic reconstruction surgeries for ureteral stenosis. Seven cases of stenosis of the distal ureter, two at the level of iliac vessels, a case of bilateral distal stenosis and one in the medium third. Eight ureteroneocystotomies were performed by extravesical technique with anti-reflux mechanism, two cases of vesical reimplant with Boari technique and one case using the psoas hitch technique. RESULTS: The average surgical time was 166 minutes (115-245 min), mean blood loss was 162 mL (100-210 mL) and the average hospital stay was 2.9 days (2-4 days). There were two complications: a lesion of the sigmoid colon identified peroperatively and treated with laparoscopic sutures with good evolution, and a case of ureteral stone obstruction at the 30th day postoperative, treated by laser ureterolitotripsy. All patients had resolution of the stenosis at an average follow-up period of 18 months (3-54 months). CONCLUSIONS: Laparoscopic surgery represents a feasible, safe and low morbidity technique for ureteral reimplant in ureteral stenosis.